Data from: Residual eDNA detection sensitivity assessed by quantitative real-time PCR in a river ecosystem - Balasingham, Katherine D.; Walter, Ryan P.; Heath, Daniel D. (Zenodo, 2016)
Several studies have demonstrated that environmental DNA (eDNA) can be used to detect the presence of aquatic species, days to weeks after the target species has been removed. However, most studies used eDNA analysis in lentic systems (ponds or lakes), or in controlled laboratory experiments. While eDNA degrades rapidly in all aquatic systems, it also undergoes dilution effects and physical destruction in flowing systems, complicating detection in rivers. However, some eDNA (i.e. residual eDNA) can be retained in aquatic systems, even those subject to high flow regimes. Our goal was to determine residual eDNA detection sensitivity using quantitative real-time polymerase chain reaction (qRT-PCR), in a flowing, uncontrolled river after the eDNA source was removed from the system; we repeated the experiment over two years. Residual eDNA had the strongest signal strength at the original source site and was detectable there up to 11.5 hours after eDNA source removal. Residual eDNA signal strength decreased as sampling distance downstream from the eDNA source site increased, and was no longer detectable at the source site 48 hours after the eDNA source water was exhausted in both experiments. This experiment shows that residual eDNA sampled in surface water can be mapped quantitatively using qRT-PCR, which allows a more accurate spatial identification of the target species location in lotic systems, and relative residual eDNA signal strength may allow the determination of the timing of the presence of target species. Appendix S1. Ct values for qRT-PCR efficiency for Salmo salar. Ct values for Figure 2. 10-fold Salmo salar dilution series with Salmo_Mito-951 (d-loop; Karlsson et al. 2012) primer set. Suppl Info - Appendix S1. Ct values for qRT-PCR efficiency.xlsx Appendix S2. Little River 2014 qRT-PCR Ct values. Ct values for Figure 3A. Little River 2014 river samples. Primer set Salmo_Mito-951 (Karlsson et al. 2012). Suppl Info - Appendix S2. Little River 2014 qRT-PCR Ct values.xlsx Appendix S3. Little River 2015 ...